Fish larvae dynamics in temperate estuaries: A review on processes, patterns and factors that determine recruitment. Issue 3 (8th March 2023) - Arevalo, Elorri; Cabral, Henrique N.; Villeneuve, Bertrand; Possémé, Carl; Lepage, Mario
Abstract: Early life stages of fish (eggs and larvae) are particularly vulnerable with mortality rates of up to 99% recorded for a large number of species. High mortality rates result from the limited swimming ability of larvae preventing them from escaping sub‐optimal environmental conditions, predators or low prey density areas. In this context, estuaries are key nursery areas for larval and juvenile fish. Estuarine habitats offer environmental conditions favourable to the survival and growth of early stages, through abundant good‐quality prey and protection from predators. A vast literature on larvae occurring in temperate estuaries exists, but an overall perspective is lacking. The occurrence of fish larvae in temperate estuaries depends on several factors. First, the choice of spawning time and location is primordial, as they have evolved to optimise the entry and the retention of larvae in the estuary as well as the conditions experienced by young stages. Secondly, larval growth and survival depend on key environmental factors (e.g. salinity, water temperature, freshwater inputs, turbidity and dissolved oxygen concentration). Knowledge of the larval dynamics in temperate estuaries is scarce for some topics and biased towards some species or geographical areas. The main goal of the present literature review is to synthesise existing knowledge regarding spawning timing and location and larval ecology for fish species occurring in coasts and estuaries, identifying the main patterns, consensus or conflicting hypotheses and highlighting major gaps. Research needs and future perspectives were outlined.